Heart Failure With Preserved Ejection Fraction Induces Beiging in Adipose Tissue. (January 2016) - Valero-Muñoz, María; Li, Shanpeng; Wilson, Richard M.; Hulsmans, Maarten; Aprahamian, Tamar; Fuster, José J.; Nahrendorf, Matthias; Scherer, Philipp E.; Sam, Flora
Abstract : Background—: Despite the increasing prevalence of heart failure with preserved ejection fraction (HFpEF) in humans, there are no evidence-based therapies for HFpEF. Clinical studies suggest a relationship between obesity-associated dysfunctional adipose tissue (AT) and HFpEF. However, an apparent obesity paradox exists in some HF populations with a higher body mass index. We sought to determine whether HFpEF exerted effects on AT and investigated the involved mechanisms. Methods and Results—: Mice underwent d -aldosterone infusion, uninephrectomy, and were given 1% saline for 4 weeks. HFpEF mice developed hypertension, left ventricular hypertrophy, and diastolic dysfunction and had higher myocardial natriuretic peptide expression. Although body weights were similar in HFpEF and sham-operated mice, white AT was significantly smaller in HFpEF than in sham (epididymal AT, 7.59 versus 10.67 mg/g; inguinal AT, 6.34 versus 8.38 mg/g). These changes were associated with smaller adipocyte size and increased beiging markers (ucp-1, cidea, and eva) in white AT. Similar findings were seen in HFpEF induced by transverse aortic constriction. Increased activation of natriuretic peptide signaling was seen in white AT of HFpEF mice. The ratio of the signaling receptor, natriuretic peptide receptor type A, to the clearance receptor, nprc, was increased as was p38 mitogen-activated protein kinase activation. However, HFpEF mice failed to regulate body temperature during cold temperature exposure. In HFpEF, despite a larger brown AT mass (5.96 versus 4.50 mg/g), brown AT showed reduced activity with decreased uncoupling protein 1 (ucp-1), cell death-inducing DFFA-like effector a (cidea), and epithelial V-like antigen (eva) expression and decreased expression of lipolytic enzymes (hormone-sensitive lipase, lipoprotein lipase, and fatty acid binding protein 4) versus sham. Conclusions—: These findings show that HFpEF is associated with beiging in white AT and with dysfunctional brown AT. Abstract : Supplemental Digital Content is available in the text.